Exploring The Impact of Polya’s Problem-Solving Strategy on Biology Students’ Achievement and Retention: A Case Study of Secondary Schools in Delta State, Nigeria - Ewere, Chukwuka Rita (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
This study investigated the impact of Polya’s problem-solving strategy on biology students’ achievement and retention in secondary schools in Delta State, Nigeria. The quasi-experimental research design employed pre-test and post-test measures with control and experimental groups. A sample of biology students was randomly selected from senior secondary schools, with the experimental group taught using Polya’s four-step problem-solving strategy—understanding the problem, devising a plan, carrying out the plan, and looking back—while the control group received instruction through the conventional lecture method. Data were collected using a validated Biology Achievement Test (BAT) and a Retention Test (RT). Analysis of covariance (ANCOVA) and t-tests were used to analyze the data at a 0.05 level of significance. Findings revealed that students taught with Polya’s strategy significantly outperformed those taught with traditional methods in both achievement and retention tests. Results further indicated that the structured, student-centered approach of Polya’s strategy fostered deeper conceptual understanding and enhanced long-term retention. These findings align with constructivist learning theories that emphasize active participation and knowledge construction. The study concludes that Polya’s problem-solving strategy is an effective pedagogical approach for improving biology achievement and retention. It recommends the adoption of Polya’s method by teachers, integration into biology curricula, and teacher training programs to enhance effective instructional practices in Nigerian schools.